Mouse DBS profiling - Bendes, Annika (SciLifeLab Serve, 2026)
This app provides complementary visualizations of affinity proteomics data generated from dried blood spot (DBS) samples collected from a mouse model. The visualizations present longitudinal protein profiles in infected and uninfected mice, heatmaps of protein-protein correlations, and data quality assessments.